Osteomalacie - Rosa, Jan (Vnitrni lekarstvi, 2023)
Osteomalacia with characteristic histomorphometric, radiographic, laboratory and clinical features is a prominent syndrome of disturbed bone mineralisation in adulthood. From an etiological point of view, osteomalacia is usually caused by substrate (calcium, phosphate) deficiency, presence of excess mineralization inhibitors or deficiency or ineffectivness of mineralization facilitator (vitamin D). In proportion to the high number of congenital and acquired causes of osteomalacia, its clinical and laboratory picture is heterogeneous and rarely fully expressed. The treatment of a particular case is determined by the cause of osteomalacia and may (but does not necessarily) include correction of the underlying disease, administration of calcium and various forms of vitamin D, as well as orthopaedic interventions. For some of the hereditary forms, biological or replacement therapy is prospectively available. The article attempts to cover the whole range of osteomalacia variants, mentioning a fact discussed only in recent years - the occurrence of oligosymptomatic, incompletely expressed forms.
Keywords: Vitamins; osteoid; Vitamin D Deficiency; bone mineral; vápník; Osteomalacia; nedostatek vitaminu D; osteomalacie; Calcium; Vitamin D; vitaminy; Humans; vitamin D; bone matrix; mineralization; syndrom; osteomalacia; Syndrome; lidé